Adaptation Or Exploitation? An Analysis of the Family Structure of the Hijra Community in Bangladesh - Shah , Faruk; Shahidullah, Kazi K; Sultana , Fahmida; Shah , Mojahar Rahman (Journal of Ethnic and Cultural Studies, 2024)
This article examines the social and economic adaptation mechanisms practiced by the hijra community in Bangladesh, with a particular focus on the family structure and social relations. It posits that an analysis of hijra family dynamics may be effectively conducted by including theories of social adaptation and economic exploitation, drawing upon qualitative data. As the hijra children undergo maturation and manifest their sexual and behavioural distinctiveness, the familial outlook on the children experiences a transformation as time progresses. Hijra children are ultimately subjected to parental and societal neglect, rejection and discrimination, which in turn push them to establish an independent existence under hijra community. Within the community, the establishment and nurturing of the familial bond between the guruma, who serves as the head of the family, and the chela, who assumes the role of the disciple, is facilitated through a shared sense of affinity and unwavering loyalty. Furthermore, a significant correlation exists between hijra families and their economic system. The chela hijras, who have experienced separation from their biological families, seek shelter under the care of a guruma. Consequently, they endure processes of social and economic adaptation. However, they also experience economic exploitation from the guruma. This study applies a combination of primary and secondary sources of data, and Case Studies, In-depth Interviews and Key Informant Interviews (KIIs) have been used to collect firsthand data. The research findings shed light on the process through which hijras are integrated into the community, as well as the various forms and degrees of economic exploitation they encounter. Thus, this article contributes to the existing body of literature on the issues of third gender and the vulnerabilities they face and what measures should be taken for their inclusive development.